ChemInform Abstract: Asymmetric Henry Reaction Catalyzed by L‐Proline Derivatives in the Presence of Cu(OAc)2: Isolation and Characterization of an in situ Formed Cu(II) Complex. Issue 35 (2nd September 2014) - Atoholi Sema, H.; Bez, Ghanashyam; Karmakar, Sanjib
Abstract In addition to the synthesis of the ligand PRO, the preparation of five proline‐derived chiral ligands is described all showing inferior catalytic activity compared to PRO under the investigated conditions.